Musical Devotions for Mixed Audiences: Printed Metrical Song in the Edwardian Reformation - Heminger, Anne (Reformation, 2022)
While scholarship on the Edwardian Reformation often stresses reformers’ critiques of liturgical music as evidence for their disdain of religious music more broadly, this article posits that the numerous volumes of English-texted, verse scripture printed at this time demonstrate the central strategic importance of vernacular devotional song for reformers from a variety of backgrounds. Focusing on William Baldwin’s The Canticles or balades of Salomon (1549), William Samuel’s The abridgemente of goddess statutes (1551), and Christopher Tye’s The Actes of the Apostles (1553), this article re-centers the early collections of metrical psalms and other biblical verse paraphrases printed in Edwardian England as musical texts, demonstrating that reformers in mid-Tudor England embraced music as a means for England’s inhabitants to acquaint themselves with the theology and practices of the reformed Church of England. In doing so, they employed singing to confessionalize a public with diverse religious beliefs.